Photodynamic inactivation of biofilms formed by Candida spp., Trichosporon mucoides, and Kodamaea ohmeri by cationic nanoemulsion of zinc 2,9,16,23-tetrakis(phenylthio)-29H, 31H-phthalocyanine (ZnPc) - Junqueira, Juliana Campos [UNESP]; Jorge, A. O. C. [UNESP]; Barbosa, J. O. [UNESP]; Rossoni, R. D. [UNESP]; Vilela, S. F. G. [UNESP]; Costa, A. C. B. P. [UNESP]; Primo, F. L.; Goncalves, J. M.; Tedesco, A. C.; Suleiman, J. M. A. H. (Springer London Ltd, 2012)
The biofilms formed by opportunistic yeasts serve as a persistent reservoir of infection and impair the treatment of fungal diseases. The aim of this study was to evaluate photodynamic inactivation (PDI) of biofilms formed by Candida spp. and the emerging pathogens Trichosporon mucoides and Kodamaea ohmeri by a cationic nanoemulsion of zinc 2,9,16,23-tetrakis(phenylthio)-29H,31H-phthalocyanine (ZnPc). Biofilms formed by yeasts after 48 h in the bottom of 96-well microtiter plates were treated with the photosensitizer (ZnPc) and a GaAlAs laser (26.3 J cm(-2)). The biofilm cells were scraped off the well wall, homogenized, and seeded onto Sabouraud dextrose agar plates that were then incubated at 37A degrees C for 48 h. Efficient PDI of biofilms was verified by counting colony-forming units (CFU/ml), and the data were submitted to analysis of variance and the Tukey test (p < 0.05). All biofilms studied were susceptible to PDI with statistically significant differences. The strains of Candida genus were more resistant to PDI than emerging pathogens T. mucoides and K. ohmeri. A mean reduction of 0.45 log was achieved for Candida spp. biofilms, and a reduction of 0.85 and 0.84, were achieved for biofilms formed by T. mucoides and K. ohmeri, respectively. Therefore, PDI by treatment with nanostructured formulations cationic zinc 2,9,16,23- tetrakis (phenylthio)- 29H, 31H- phthalocyanine (ZnPc) and a laser reduced the number of cells in the biofilms formed by strains of C. albicans and non-Candida albicans as well the emerging pathogens T. mucoides and K. ohmeri.
Keywords: Biofilm; Candida spp.; Trichosporon mucoides; Kodamaea ohmeri; Photodynamic inactivation; Zinc phthalocyanine